An enhancement of JPEG algorithm applied in image compression - Marjen Ajias and Geneva Mejia. 4 0 16; 5
ABSTRACT:The idea of image compression basically came from wanting the image to reduce its data redundancies to be able to store and transmit more data imagery efficiently. JPEG is an algorithm based on lossy compression which is effective in compressing continuous tone image. The algorithm is one of the most popular compression techniques which are used commonly in the real world. Proposed work, which uses filtering methods, was able to improve the quality of images without sacrificing its storage quantity. The original, compressed and decompressed images were evaluated using the image quality metrics, Peak signal to-noise-ration (PSNR) and Mean square error (MSE). Compressing an image is beneficial because it decreases memory consumption, the use of costly resources such as hardware storage or hardware space requirements and transmission bandwith.
Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2